Newborn Analgesia Mediated by Oxytocin during Delivery - Mazzuca, Michel; Minlebaev, Marat; Shakirzyanova, Anastasia; Tyzio, Roman; Taccola, Giuliano; Janackova, Sona; Gataullina, Svetlana; Ben-Ari, Yehezkel; Giniatullin, Rashid; Khazipov, Rustem (Frontiers in Cellular Neuroscience, 2011)
The mechanisms controlling pain in newborns during delivery are poorly understood. We explored the hypothesis that oxytocin, an essential hormone for labor and a powerful neuromodulator, exerts analgesic actions on newborns during delivery. Using a thermal tail-flick assay, we report that pain sensitivity is two fold lower in rat pups immediately after birth than two days later. Oxytocin receptor antagonists strongly enhanced pain sensitivity in newborn, but not in two days-old rats, whereas oxytocin reduced pain at both ages suggesting an endogenous analgesia by oxytocin during delivery. Similar analgesic effects of oxytocin, measured as attenuation of pain-vocalization induced by electrical whisker pad stimulation, were also observed in decerebrated newborns. Oxytocin reduced GABA-evoked calcium responses and depolarizing GABA driving force in isolated neonatal trigeminal neurons suggesting that oxytocin effects are mediated by alterations of intracellular chloride. Unlike GABA signaling, oxytocin did not affect responses mediated by P2X3 and TRPV1 receptors. In keeping with a GABAergic mechanism, reduction of intracellular chloride by the diuretic NKCC1 choride co-transporter antagonist bumetanide mimicked the analgesic actions of oxytocin and its effects on GABA responses in nociceptive neurons. Therefore, endogenous oxytocin exerts an analgesic action in newborn pups that involves a reduction of the depolarizing action of GABA on nociceptive neurons. Therefore, the same hormone that triggers delivery also acts as a natural pain killer revealing a novel facet of the protective actions of oxytocin in the fetus at birth.